360-Degree Virtual Reality Consultation for the Structural Heart Disease Patient. Issue 3 (3rd May 2020) - Castellanos, Jorge M.; Yefimov, Alex; Dang, Phuong N.
ABSTRACT: Background: : Given the need to improve upon physician-patient communication, we employed a 360-degree Virtual Reality (360°VR) visualization platform for face-to-face consultations for TAVR and LAAO procedures. The platform creates patient-specific 360°VR models from volumetric scans (e.g., CT, MRI) that can be manipulated and viewed from any angle. Methods: : Forty-six patients were prospectively surveyed regarding their 360°VR consultation experience for aortic valve stenosis and atrial fibrillation. For each patient, a custom 360°VR model was created from their high-resolution CT scans using Precision VR® by Surgical Theater and utilized during the 360°VR consultation. The proposed procedure was simulated in VR to show the interaction of the specific implant with the patient's anatomy. Patient conversion rate was also evaluated. Results: : Compared to prior standard (non-VR) consultations for the same medical condition, patients reported significantly higher satisfaction with the 360°VR consultation and increased understanding of their pathology and proposed procedure. Additionally, 98% of patients agreed the physician communicated well using Surgical Theater. Patients also reported that experiencing 360°VR helped improve their understanding (98%) and comfort level (93%) with the proposed procedure. Importantly, 91% of patients agreed they felt included in decisions about their treatment. Additionally, 76% rated the hospital a 9 or 10 and 81% said they would recommend this hospital. Conversion rates after 360°VR consultations were higher than those for pre-360°VR consultations (100% vs 86%, TAVR; 92% vs 68%, Watchman). Conclusion: : These findings support the 360°VR technology as a powerful tool to enhance patient education, engagement and satisfaction for structural heart disease patients. Abbreviations: 360°VR: 360-degree Virtual Reality; TAVR: transcatheter aortic valve replacement; LAAO: left atrial appendage occlusion; HCAHPS: Hospital Consumer Assessment of Healthcare Providers and Systems; CMS: Centers for Medicare and Medicaid Services